Whatsapp-Based Supervision by Ward Head Nurses to Improve Compliance With Standard Precautions: A Quasi-Experimental Study - Supit, Deetje Sientje; Bawaeda, Olivia; Mandagi, Autry Alvian (Fakultas Ilmu Keperawatan Universitas Klabat, 2026)
Standard precautions are crucial for preventing nosocomial infections, but nurse compliance remains suboptimal. This study aimed to evaluate the effectiveness of WhatsApp-based monitoring in improving nurse compliance. A quasi-experimental design with a control group involved 30 nurses in the inpatient ward of a hospital in Tomohon (2025), divided into an intervention (n=15) and a control (n=15) group. The four-week intervention included daily reminders, educational materials, discussions, and feedback via WhatsApp, while the control group received standard briefings. Compliance was measured through observation using WHO and CDC checklists and analyzed using a t-test (p < 0.05). Results showed no initial differences between the groups, but significant improvements in both groups after the intervention (p < 0.001), with better outcomes in the intervention group (p = 0.04). The intervention was deemed beneficial by participants and demonstrated that WhatsApp is effective as a simple and cost-effective monitoring medium. Integration of this approach is recommended to improve patient safety and prevent infections in healthcare facilities. Kewaspadaan standar penting dalam mencegah infeksi nosokomial, namun kepatuhan perawat masih belum optimal. Penelitian ini bertujuan mengevaluasi efektivitas pengawasan berbasis WhatsApp dalam meningkatkan kepatuhan perawat. Desain quasi-eksperimental dengan kelompok kontrol melibatkan 30 perawat di ruang rawat inap rumah sakit di Tomohon (2025), yang dibagi menjadi kelompok intervensi (n=15) dan kontrol (n=15). Intervensi selama empat minggu mencakup pengingat harian, materi edukasi, diskusi, dan umpan balik melalui WhatsApp, sedangkan kelompok kontrol menerima briefing standar. Kepatuhan diukur melalui observasi menggunakan checklist WHO dan CDC, serta dianalisis dengan uji t (p < 0,05). Hasil menunjukkan tidak ada perbedaan awal antara kelompok, namun terjadi peningkatan signifikan pada keduanya setelah intervensi (p < 0,001), dengan hasil lebih baik pada kelompok intervensi (p = 0,04). Intervensi ini dinilai bermanfaat oleh peserta dan menunjukkan bahwa WhatsApp efektif sebagai media pengawasan yang sederhana dan hemat biaya. Integrasi pendekatan ini direkomendasikan untuk meningkatkan keselamatan pasien dan mencegah infeksi di fasilitas kesehatan.